Early-life adversity as a predictor of fibromyalgia syndrome: the central role of perceived stress over endocrine stress indicators - Beiner, Eva; Hermes, Michelle; Reichert, Julian; Kleinke, Kristian; Vock, Stephanie; Löffler, Annette; Ader, Leonie; Sirazitdinov, Andrei; Keil, Sebastian; Schmidt, Tim; Schick, Anita; Löffler, Martin; et al. (Pain, 2025)
This study investigates the associations between early childhood adversities, stress perception, and fibromyalgia syndrome (FMS). Although the interconnection between dysregulated stress systems and FMS is well documented, the interconnection between early adversities and FMS remains less understood. This study explores the relationship of early-life stress and FMS by examining its mediation through perceived stress, and acute and chronic endocrine stress indicators. Stress was assessed using the perceived stress scale, as well as using salivary and hair cortisol as endocrine indicators of acute and chronic stress, respectively. The sample consisted of 99 individuals with FMS and 50 pain-free controls. A structural equation model was used to assess the mediating effects of stress indicators between early adversities and the severity of FMS. Compared with controls, individuals with FMS had notably higher early adversity scores (d = 0.63) and greater occurrence of exposure to adversity (78.8% vs 66%). Structural equation modeling indicated that the influence of early adversities on FMS symptoms is mediated by perceived stress levels, with no direct effect observed. Our findings indicate that early-life adversity is a significant determinant of the development of FMS, with the relationship between these factors mediated by perceived stress rather than by endocrine stress indicators. These results underscore the critical role of stress perception in the development and management of FMS, suggesting that perceived stress may serve as a valuable therapeutic target. Incorporating trauma-informed and stress-targeted care into treatment strategies could significantly improve outcomes for individuals with FMS, emphasizing the importance of addressing psychological factors alongside physical symptoms.
Gesehen am 14.08.2025